Philosophy of ubuntu and collaborative project-based learning in post-apartheid South Africa: A case study of underperforming learners at Hope Saturday school - Saloshna Vandeyar; Matsie Agnes Mohale (South African Journal of Education, 2022)
Utilising a qualitative case study, we set out to investigate how learners at Hope Saturday School evoked the principles of ubuntu/humanity as they collaborated during project-based learning. The article is part of a broader study in which a mix of semi-structured interviews, focus group interviews, observations, document analysis and field notes were used to capture data. The learner participants were Black, and almost all of them resided in informal settlements, townships, and farming communities. Data were analysed using content analysis. The philosophy of ubuntu was used to underpin this study. The finding of this study shows that values like interdependence, sharing, caring, teamwork, solidarity, unity and helping one another were evoked as learners collaborated in project-based learning. The article concludes that a supportive environment that aids the development of ubuntu values can improve learning experiences of underperforming learners.